Transmission Efficiency Test and Analysis of High-precision RV Reducer - Tong Guan; Honghai Xu; Xiongwei Xie; Linghui Wei (Jixie chuandong)
Based on the working principle of RV reducer， the combined， modular transmission efficiency test platform and its measurement and control system and software system that can meet the installation requirements of RV reducer with different specifications are designed and developed. The transmission efficiency test is carried out on the RV-40E prototype independently developed by orthogonal test method. The test data is analyzed by variance and variance. The results show that the factors affecting the transmission efficiency of the RV reducer are the interaction of output torque， input speed and output torque. Input speed， output torque is a significant factor， and the rest are non-significant factors.